Factors that influence the selection and utilization of children's medical insurance - Shishu Zhang; Gregory J. Soukup; Tahir Nisar (Cogent Business & Management, 2015)
The researchers analyzed how different regions in the USA, family structure, ethnicity, and family income levels influenced the selection and utilization of medical care programs and services by American children. To prevent any possible bias in the analysis and to produce reliable results, an endogenous switching model was utilized in the study. The researchers found no statistically significant differences in the number of doctor visits and hospital stays between children with insurance and children without insurance. However, significant differences were determined regarding family structure, family income, geographic regions, and ethnicity. Children from single-parent families with insurance coverage (private, Medicaid, or SCHIP) had statistically higher rates of doctor visits and hospital stays than children from two-parent families with insurance coverage. Family income, region, and ethnicity variables all had significant impacts on the type of health insurance coverage that was reported for children.
Keywords: 650